2019
DOI: 10.1029/2019jc015322
|View full text |Cite
|
Sign up to set email alerts
|

On Mechanisms Controlling the Seasonal Hypoxia Hot Spots off the Changjiang River Estuary

Abstract: Large areas of seasonal hypoxia have been detected off the Changjiang River Estuary over the last decade. Although seasonal bottom hypoxia was transient due to complex dynamical processes, it occurred with high frequency in certain regions. Summer hypoxia hot spots off the estuary were first identified using a comprehensive, high-resolution ecosystem model and 17 years of observations collected from historical literature and research cruises. Comparisons between long-term observations, a 4-year averaged simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…11), DO-depleted area could have occurred in the northern part both in 2016 and 2018, with the larger extent in the former year. The positive correlation between the river discharge and the hypoxic area has been found by the model simulation (Zheng et al, 2016). Hypoxia in the northern part in 2016 was reported (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…11), DO-depleted area could have occurred in the northern part both in 2016 and 2018, with the larger extent in the former year. The positive correlation between the river discharge and the hypoxic area has been found by the model simulation (Zheng et al, 2016). Hypoxia in the northern part in 2016 was reported (Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 54%
“…Also, it has been shown that vertical mixing caused considerable variations in DO concentrations in the near-bottom layer (Ni et al, 2016). Higher wind speed causes stronger vertical mixing and vanishing of hypoxia (Zheng et al, 2016). In July 2015, 1.5 months before our survey, hypoxia was terminated by a typhoon, but 2 d later, hypoxic conditions were reestablished (Guo et al, 2019).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Although HGI is useful to determine whether a system is favorable for hypoxia formation, it cannot fully explain the hypoxia variability in the WCTZ for different scenarios with HG1 < 1. Oxygen diffusion through wind‐induced mixing can erode the hypoxic layer and reduce HA, as found in Changjiang Estuary (Zhang et al., 2019). AKv in the WCTZ is much smaller than in the ECTZ, which also contributes to the larger HA in the WCTZ (Figure 9).…”
Section: Discussionmentioning
confidence: 94%
“…The depositional environment and dynamics of the ECS have been relatively stable since the last 2000 years with slight sea-level change, because the Yangtze River delta and the local current circulation system had been basically formed (Li et al, 2014). However, large areas of seasonal harmful algal blooms and hypoxia have been detected in the ECS in recent decades (Qu et al, 2019; Zhang et al, 2019), being increasing threats to coastal ecosystems. Meanwhile, a mass of dams caused fluvial erosion, which has an important impact on the coastal environment and material supply of the ECS (Sun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%